Multimodal fluorescence-optoacoustic in vivo imaging of the near-infrared calcium ion indicator NIR-GECO2G - Sarah F. Shaykevich; Justin P. Little; Yong Qian; Marie-Eve Paquet; Robert E. Campbell; Daniel Razansky; Shy Shoham (Photoacoustics)
Measuring whole-brain distributed functional activity is an important unmet need in neuroscience, requiring high temporal resolution and cellular specificity across large volumes. Functional optoacoustic neuro-tomography (FONT) with genetically encoded calcium ion indicators is a promising approach towards this goal. However, it has not yet been applied in the near-infrared (NIR) range that provides deep penetration and low vascular background optimal for in vivo neuroimaging. Here, we study the noninvasive multimodal fluorescence and optoacoustic imaging performance of state-of-the-art NIR calcium ion indicator NIR-GECO2G in the mouse brain. We observe robust in vivo signals with widefield fluorescence, and for the first time, with FONT. We also show that in both modalities, the NIR-GECO2G signal improves more than twofold in the biliverdin-enriched Blvra-/- mouse line compared to wild type. Our findings demonstrate the potential of multimodal fluorescence and optoacoustic NIR imaging, opening new possibilities for whole-brain real-time functional imaging in rodents.